Božena Němcova's life from three points of view (Miloš Urban, František Novotný, Lenka Lagronová) - Pająk, Aleksandra (Bohemica Olomucensia, 2018)
The paper employs Aby Warburg's concept of Nachleben to analyse Božena Němcova's figure. It concentrates on her images created after 1989 which constitute a sign of breaking the cultural taboo. In Urban's action novel, she is demythologized in the intermezzi that are ostensibly unrelated to the actual plot. Novotný's figuratively and literally "undresses" the writer, whereas Lagronová demonstrates the woman's tragedy as a victim of other people's desires.
Keywords: deheroisation; "second life"; cultural taboo; Božena Němcová; Miloš Urban; František Novotný; Lenka Lagronová